Eye Movement Desensitization and Reprocessing Therapy in Children Experiencing Mental Health Challenges - Anwar, Khan; Amalia, Madihie (IGI Global, 2024)
This chapter provides a comprehensive overview of eye movement desensitization and reprocessing (EMDR) therapy in the context of childhood mental health issues. It explores the origins, principles, and therapeutic mechanisms of eye movement desensitization and reprocessing therapy. One of the keys focuses of this chapter has been the adaptation of this therapy for children. Finally, this chapter emphasizes the importance of training and supervision for therapists working with EMDR therapy among children, as well as the need for further research and development in this field. This chapter concluded that eye movement desensitization and reprocessing therapy has emerged as a widely accepted and effective treatment approach for addressing mental health problems among children. By incorporating this therapy into their practice, mental health professionals can provide evidence-based interventions to help children overcome mental health challenges and promote their overall well-being.